Quality and Standards of Social Services - Žalimienė, Laimutė; Vareikytė, Audronė (Socialinė teorija, empirija, politika ir praktika, 2001)
The specialists from the Ministry of Labour and Social Security of the Republic of Lithuania, municipalities, child rights protection service, social care organisations were participating in the discussion about the quality of social services and quality management. The content, function, implementation and control of the standards for social services were discussed.